Socialization of the Importance of Higher Education in Increasing Motivation to Continue Studies among Students of SMA F. Tandean Tebing Tinggi - Irma Herliza Rizki; Nur Wahyuni; Andi; Dinda Widyastika; Muammar Rinaldi (Outline Journal of Community Development, 2026)
Higher education plays a crucial role in improving the quality of human resources and the competitiveness of the younger generation in the global era. However, many high school students still lack motivation to pursue higher education due to limited access to information about the benefits of higher education, college admission pathways, and scholarship opportunities. This community service activity aims to increase the knowledge and motivation of students at SMA F. Tandean Tebing Tinggi to pursue higher education. The activity was implemented using a participatory approach through preparation, material delivery, interactive discussions, questions and answers, evaluation, and documentation. The activity involved 105 12th-grade students from three classes. The material presented covered the importance of higher education, new student admission pathways, scholarship programs, selecting study programs based on interests and talents, and career prospects for college graduates. The results showed that participants enthusiastically and actively participated in the socialization throughout the discussion. In addition to improving students' understanding of access to higher education, this activity also succeeded in fostering their motivation to pursue further studies and broadening their horizons regarding educational opportunities and career development. This program is expected to become a model for sustainable collaboration between universities and schools in increasing higher education participation rates.